Residual mechanical effectiveness of external ankle tape before and after competitive professional soccer performance - Best, R.; Mauch, F.; Böhle, C.; Huth, J.; Brüggemann, P. (Clinical Journal of Sport Medicine, 2014)
Objective: To evaluate the presupposed preventive residual mechanical effectiveness of the widespread use of adhesive elastic ankle tape after a nonlaboratory, realistic soccer-specific outfield intervention reflecting a soccer halftime.